AJM300 (carotegrast methyl), an oral antagonist of α4-integrin, as induction therapy for patients with moderately active ulcerative colitis: a multicentre, randomised, double-blind, placebo-controlled, phase 3 study. (July 2022) - Matsuoka, Katsuyoshi; Watanabe, Mamoru; Ohmori, Toshihide; Nakajima, Koichi; Ishida, Tetsuya; Ishiguro, Yoh; Kanke, Kazunari; Kobayashi, Kiyonori; Hirai, Fumihito; Watanabe, Kenji; Mizusawa, Hidehiro; Kishida, Shuji; et al.
Summary: Background: AJM300 is an oral, small-molecule α4-integrin antagonist. We assessed the efficacy and safety of AJM300 in patients with moderately active ulcerative colitis. Methods: This multicentre, randomised, double-blind, placebo-controlled, phase 3 study consisted of two phases: a treatment phase and an open-label re-treatment phase. The study was done at 82 hospitals and clinics in Japan. Patients with a Mayo Clinic score of 6–10, endoscopic subscore of 2 or more, rectal bleeding subscore of 1 or more, and an inadequate response or intolerance to mesalazine were enrolled. Patients were randomly allocated (1:1) via a website to either AJM300 (960 mg) or placebo by the minimisation method, which was adjusted centrally by dynamic assignment against the Mayo Clinic score (≥6 to ≤7, ≥8 to ≤10 points), any use of corticosteroid, anti-TNFα antibody, or immunosuppressants during the disease-active period (yes vs no), duration of induction therapy until randomisation (<4 weeks vs ≥4 weeks) as the minimisation factors. Patients, investigators, site staff, assessors, and the sponsor were masked to treatment assignments. The study drug was administered orally, three times daily, for 8 weeks, and continued for up to 24 weeks if endoscopic remission was not achieved or rectal bleeding did not stop. The primary endpoint was the proportion of patients with a clinical response at week 8, and was analysed in the full analysis set. Clinical response was defined as a reduction in Mayo Clinic score of 30% or more and 3 or more, a reduction in rectal bleeding score of 1 or more or rectal bleeding subscore of 1 or less, and an endoscopic subscore of 1 or less at week 8. The study is registered with ClinicalTrials.gov, NCT03531892, and is closed to recruitment. Findings: Between June 6, 2018, and July 22, 2020, 203 patients were randomly assigned to AJM300 (n=102) or placebo (n=101). At week 8, 46 (45%) patients in the AJM300 group and 21 (21%) patients in the placebo group had a clinical response (odds ratio 3·30, 95% CI 1·73−6·29; p=0·00028). During the 8-week treatment and 16-week extension treatment periods, adverse events occurred in 39 (39%) of 101 patients in the placebo group and 39 (38%) of 102 patients in the AJM300 group. We found no difference in the incidence of adverse events between groups or after repeated administration of AJM300. The most common adverse event was nasopharyngitis (11 [11%] of 101 patients in the placebo group and ten [10%] of 102 patients in the AJM300 group). The most common treatment-related adverse event was also nasopharyngitis (four [4%] of 101 patients in the placebo group and three [3%] of 102 patients in the AJM300 group). Most adverse events were mild-to-moderate in severity. No deaths were reported. A serious adverse event was reported in the AJM300 group (one patient with anal abscess), but this was judged to be unrelated to study drug. Interpretation: AJM300 was well tolerated and induced a clinical response in patients with moderately active ulcerative colitis who had an inadequate response or intolerance to mesalazine. AJM300 could be a novel induction therapy for the treatment of patients with moderately active ulcerative colitis. Funding: EA Pharma and Kissei Pharmaceutical. Translation: For the Japanese translation of the abstract see Supplementary Materials section.